(untitled) (Development Service Industry Management, 2025)
The interior design of a restaurant is a critical factor influencing its market competitiveness, especially for established chain restaurants. The visual aesthetics of a space play a pivotal role in shaping a guest’s first impression, affecting their emotional state, extending their duration of stay, and fostering long-term customer loyalty. For long-standing establishments, interior renovation becomes particularly crucial for maintaining relevance and attracting new clientele. This article delves into the specific features of interior design within chain pizzerias located in Kyiv. It analyzes contemporary trends in restaurant interior design, emphasizing key principles such as functionality, accessibility, and emotional engagement. The research focuses on the practical application of modern design approaches, with a specific case study on the renovation of a dining room within the Pizza Hut chain. A central theme of this study is the development of practical recommendations for updating the interior based on the biophilic design concept. This approach integrates natural elements and systems into the built environment to enhance the well being and comfort of occupants. The article outlines a detailed plan for the Pizza Hut renovation, considering not only modern design principles but also economic feasibility. By demonstrating how biophilic design can be applied to a real-world scenario, this paper provides a valuable framework for restaurant owners and designers seeking to revitalize their spaces and improve customer experience.